Para um glossário neológico da obra "O Guesa", de Sousândrade: uma proposta - Alves, Gisele (2006)
Change constitutes one of the universal characteristics of human language. Lexicon represents itself as the linguistic level where this change finds a broad repercussion, once being conceived as an open system of dynamic character, the lexical universe of a language is in constant evolution, suffering adaptations that were necessary to spread new values and meanings created in a linguistic community. We comprehend language and culture represent two entities inwardly related, being the lexical expansion motivated by the creation of the vocabulary from a language due to the social and cultural transformations that are installed in every and any community. In that sense, the way which the linguistic systems adjusts to the social transformations shows oneself through the emergence of neologisms which correspond with the creation of new words and meanings incorporated to the lexical system of a language. Being situated in the perspective of that new creation (neologism) meets creative and communicative necessities of the speaking and or writer, this paper aims at collecting and analyzing the possible neologisms created by Joaquim de Sousa Andrade, Sousândrade, in his work O Guesa . Afterwards, the present research sets out to the proposal of building a glossary in the light of neologisms collected and analysed. Analyzing these neologisms, the hypothesis which this research goes on is one that considers the majority of the (neologism) new creations in O Guesa coming from the process of formation of words called composition. The register of the vocabulary form in the dictionary represents the criterion under what the word will be or won t be considered as a neologism. The dictionaries that will serve as texts of exclusion will be: Moraes (1813), Aulete (1881) e Figueiredo (1925).